Macroalgae of a stream in southeastern Brazil: composition, seasonal variation and relation to physical and chemical variables - Necchi Júnior, Orlando [UNESP]; Dip, Marícia Ribeiro [UNESP]; Góes, Rejane Maira [UNESP] (Kluwer Academic Publ, 1991)
Macroalgal seasonality was studied monthly in a second-order stream in the north-west of São Paulo State, S.E. Brazil. Seasonal variation was based on frequency and percentage cover. Seven species were found during the study period, three of which ('Chantransia' stage of Sirodotia delicatula, Homoeothrix juliana and Klebsormidium subtile) were encountered throughout the year and showed well-defined seasonal patterns as well as the highest value of frequency and percentage cover. 'Chantransia' and H. juliana dominated in summer and fall, while for K. subtile winter was the most favourable period. The remaining species (Oscillatoria agardhii, Microcoleus subtorulosus, Oedogonium sp. and Chaetophora elegans) had no clear seasonal pattern, in addition to their low values of frequency and percentage cover. Individually, K. subtile correlated with higher number of physical and chemical variables (oxygen, pH, precipitation, temperature, daylength, conductance and turbidity) than 'Chantransia' and H. juliana (discharge and depth). Principal component analyses revealed that no single variable was responsible for the macroalgal seasonal dynamics. The variables most closely related to seasonal variation of the macroalgal community were daylength, precipitation, discharge, turbidity and dissolved oxygen. Precipitation and flow were suggested as key factors in determining seasonality of the macroalgae. © 1991 Kluwer Academic Publishers.
Keywords: Brazil; Ecology; Macroalgae; Seasonality; Stream; Brazil, Sao Paulo State; Chaetophora elegans; Homoeothrix juliana; Klebsormidium subtile; Microcoleus subtorulosus; Oedogonium; Oscillatoria agardhii; Sirodotia delicatula